Մ. Պրուստի գրական-գեղարվեստական հայացքների դրսևորումը «Ընդդեմ Սենտ-Բյովի» վեպ-էսսեում - Հերմինե Մեսրոպյան (ՀՀ ԳԱԱ հրատ.)
The famous French novelist Marcel Proust (1871-1922) is one of the greatest European modernist writers o f the first half of XX century. The central place in the works of M.Proust take his literary-aesthetic and philosophical principles.
Keywords: Language and Literature